Regulation and Crosstalk of Cells and Factors in the Pancreatic Cancer Microenvironment - Xu, Jia; Lou, Songmei; Huang, Hui; Xu, Jian; Luo, Feng (Current Cancer Drug Targets, 2025)
Pancreatic cancer is a highly malignant form of cancer that distinguishes itself from other gastrointestinal tumors through significant fibrosis and unique perineural invasion. These characteristics underscore the complexity of neural regulation within the pancreatic cancer Tumor Microenvironment (TME). This review aimed to explore the regulatory mechanisms and crosstalk among stromal cells and their factors within the pancreatic cancer microenvironment. We begin by reviewing the major components of the pancreatic cancer microenvironment, analyzing interactions among crucial cell types, such as Cancer-associated Fibroblasts (CAFs) and immune cells, and revealing the dynamic changes between tumor cells and surrounding nerves, immune, and stromal cells. We discuss the role of neural factors, including the Nerve Growth Factor (NGF) and Brain-derived Neurotrophic Factor (BDNF), in the progression of pancreatic cancer and the mechanisms by which the sympathetic and parasympathetic nervous systems regulate tumor cell growth, migration, and invasion. Interactions among stromal cells, cytokines, and neural factors in the pancreatic cancer microenvironment promote fibrosis and perineural invasion. A deeper understanding of the regulation and crosstalk among components in the pancreatic cancer microenvironment offers new perspectives for inhibiting fibrosis and perineural invasion in pancreatic cancer.
Keywords: microenvironment